The Hitler Youth : marching toward madness - Dvorson, Alexa (New York : Rosen Pub. Group, 1999)
Describes how many young Germans were drawn into the Nazi movement and how Germany came more and more under the total control of Hitler and the Nazis.
Includes bibliographical references (p. 59-61) and index.
Book Report.
Wilson's Senior High School.
Young Adult
Keywords: Hitler-Jugend -- Juvenile literature; Hitler Youth; Hitler Youth; National socialism -- Juvenile literature; National socialism; National socialism; Germany -- Politics and government -- 1933-1945 -- Juvenile literature; Germany -- Politics and government -- 1933-1945.; Germany -- History -- 1933-1945.; Germany -- Politics and government